Carbon Nanodots Inhibit Tumor Necrosis Factor-α-Induced Endothelial Inflammation through Scavenging Hydrogen Peroxide and Upregulating Antioxidant Gene Expression in EA.hy926 Endothelial Cells - Jessica Chavez; Ajmal Khan; Kenna R. Watson; Safeera Khan; Yaru Si; Alexandra Y. Deng; Grant Koher; Mmesoma S. Anike; Xianwen Yi; Zhenquan Jia (MDPI AG, 2024)
Carbon nanodots (CNDs) are a new type of nanomaterial with a size of less than 10 nanometers and excellent biocompatibility, widely used in fields such as biological imaging, transmission, diagnosis, and drug delivery. However, its potential and mechanism to mediate endothelial inflammation have yet to be explored. Here, we report that the uptake of CNDs by EA.hy926 endothelial cells is both time and dose dependent. The concentration of CNDs used in this experiment was found to not affect cell viability. TNF-α is a known biomarker of vascular inflammation. Cells treated with CNDs for 24 h significantly inhibited TNF-α (0.5 ng/mL)-induced expression of intracellular adhesion molecule 1 (ICAM-1) and interleukin 8 (IL-8). ICAM-1 and IL-8 are two key molecules responsible for the activation and the firm adhesion of monocytes to activated endothelial cells for the initiation of atherosclerosis. ROS, such as hydrogen peroxide, play an important role in TNF-α-induced inflammation. Interestingly, we found that CNDs effectively scavenged H2O2 in a dose-dependent manner. CNDs treatment also increased the activity of the antioxidant enzyme NQO1 in EA.hy926 endothelial cells indicating the antioxidant properties of CNDs. These results suggest that the anti-inflammatory effects of CNDs may be due to the direct H2O2 scavenging properties of CNDs and the indirect upregulation of antioxidant enzyme NQO1 activity in endothelial cells. In conclusion, CND can inhibit TNF-α-induced endothelial inflammation, possibly due to its direct scavenging of H2O2 and the indirect upregulation of antioxidant enzyme NQO1 activity in endothelial cells.